Effectiveness of rehabilitation after a total hip arthroplasty: a protocol for an observational study for the comparison of usual care in the Netherlands versus Germany - Seeber, Gesine H (BMJ Open, 2017)
INTRODUCTION: Osteoarthritis is the most common joint disorder worldwide. Total hip arthroplasty (THA) is considered one of the most effective treatments for end-stage hip osteoarthritis. The number of THAs is expected to increase dramatically in the coming decades. Usual postoperative rehabilitation after primary THA differs between the German and the Dutch system. In the Netherlands, patients undergo fast-track surgery and are discharged into their home environment within a few days without receiving any aftercare. In Germany, patients stay in the hospital for about 12 days before being transferred to a rehabilitation centre for a period of 3 weeks. The superficially more cost-effective Dutch system of usual care after THA is judged critically in both countries due to suboptimal rehabilitation outcomes. The aim of this study is therefore to compare the Dutch with the German usual care rehabilitation after primary THA. It is hypothesised that the German procedure is more effective in terms of functional outcomes and patient satisfaction than the Dutch procedure and that in the long run the German approach is more cost-effective than the Dutch system. METHODS AND ANALYSIS: Medical effectiveness will be assessed at four different time points by means of patient self-reported questionnaires and functional tests. Assessments include the Hip disability and Osteoarthritis Outcome Score, Patient Acceptable Symptom State, Short Form 36, EuroQol 5 Dimensions 3 Level Questionnaire, Timed Up & Go Test and Five Times Sit-to-Stand Test. Additionally, long-term economic aspects in both countries will be assessed from a societal perspective, to get a first impression on whether cutting costs for rehabilitation, as practised in the Netherlands, really disburdens the healthcare system efficiently. ETHICS AND DISSEMINATION: The study is approved by the Institutional Review Boards of both University Medical Center Groningen (METc2015/483) and Hannover Medical School (no 2874-2015) and will be conducted according to the principles of the Declaration of Helsinki (64th, 2013). The results of the study will be published in international peer-reviewed scientific journals. Patient data will be presented anonymously in any publication or scientific journal. TRIAL REGISTRATION NUMBER: DRKS00011345; Pre-results.